APPLICATION OF THE THINK TALK WRITE LEARNING MODEL IN THE COURSE OF CREED AND MORALS TO IMPROVE THE LEARNING OUTCOMES OF GRADE V STUDENTS AT MIN 2 WEST PASAMAN - Saputra, Randi; Sofia, Marsela; Nur Aiza, Nadia (Amanah Publishing, 2025)
This study aims to determine the application of the Think Talk Write (TTW) learning model in improving the learning outcomes of fifth-grade students in the subject of Aqidah Akhlak at MIN 2 Pasaman Barat. The background of this study is based on the low student engagement in conventional learning, which tends to be monotonous. Therefore, an innovative learning model is needed that can encourage (1) active thinking skills, (2) speaking skills, and (3) writing skills. This type of research is field research with a qualitative approach. Data collection techniques were carried out through observation, interviews, documentation, and learning outcome tests. The research subjects were the Aqidah Akhlak subject teacher and fifth-grade students at MIN 2 Pasaman Barat. The results of the study indicate that (1) the application of the Think Talk Write model can improve student outcomes, strengthen conceptual understanding, and train communication and writing skills. (2) the improvement in student learning outcomes is seen from daily test scores data, which shows that the majority of students obtained scores above the Minimum Completion Criteria (KKM), which proves the effectiveness of this model in improving student achievement. (3) Supporting factors for the implementation of TTW include teacher commitment, active student participation, and a conducive learning environment. (4) Inhibiting factors include limited learning time, students' lack of basic thinking skills, and limitations in managing large classes. The conclusion of this study is that the TTW model is effective in teaching Aqidah Akhlak in class V at MIN 2 West Pasaman. This model not only improves learning outcomes but also helps develop students' critical thinking, communication, and collaboration skills. Therefore, the implementation of TTW is a suitable alternative learning strategy to improve the quality of education in madrasas.